Relevance Of The Bidāyat Al-Tauhīd Book Works Of Sheeykh Muhammad Basiuni Imran In Islamic Religious Education Curriculum In Schools - Masruji; Erwin Mahrus (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This study aims to examine the relevance of Muhammad Basiuni Imran's work, namely a book entitled the full Bidāyat al-Tauhīd fī 'Ilmi al-Tauhīd with the Islamic Religious Education (PAI) curriculum in schools. The research method used is literature study, which is an analysis of the contents of this book of monotheism and the PAI curriculum in schools. The results of the study show that this book has great relevance to the PAI curriculum in schools. Muhammad Basiuni Imran's work has a significant contribution to the Islamic Religious Education curriculum at all levels of education. This data can become information for the development of teaching materials and learning methods that are more effective and efficient. This work can be a useful reference for policy makers and educators in developing a more comprehensive Islamic education curriculum.